Contesting realities : the public sphere and morality in southern Yemen - Dahlgren, Susanne (Gender, culture, and politics in the Middle East., 2010)
Aden, the former capital of the only Marxist republic in the Arab world, has returned to the headlines as the scene of a popular uprising against the tribal-military rule of present-day Yemen. Dahlgren traces the social and political history of Aden from the late British colonial era, exploring the evolving ways in which the society has been established in a tension between contesting normative orders. Dahlgren offers a complex picture of Adeni society in which norms for propriety vary according to the contexts of social space. Dahlgren's original research and engaging narratives of everyday Adeni people serve to document a nuanced social flexibility She stresses individual agency and power to maneuver within a traditional patriarchal Muslim community.